Isolation of Cellulase Enzyme from Water Used in White Pepper Processing - Ngoc Hung, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1DO - 10.25073/2588-1094/vnuees.5229, 2025)
Cellulase, an enzyme that helps soften fruit peel, is produced by plants during the fruit ripening phase. Utilizing the immersing water from the white pepper processing to extract cellulase will help minimizing environmental waste and retrieving valuable compounds. Some factors affecting the cellulase yield from the immersing water of pepper were studied, including the degree of ripeness of peppercorn, immersing temperature and time. We then assess the precipitating yield of (NH 4 ) 2 SO 4 and etanol, purify cellulase by gel Sephadex G-75 filtration, and determine the preliminary compound mass by electrophoresis method. In comparison with the unripe peppercorn, the ripe peppercorn releases more cellulase. The highest cellulase activity in the water of immersed pepper was recorded at 40 o C for 48 hours, with an activity of 1.98 U/ g peppercorn. The yield of cellulase extraction was highest when precipitating with 70% ethanol, with a cellulase recovery of 48% and protein recovery of 37%. The results of gel filtration and electrophoresis showed that the cellulase mass was less than 75 kB.